2022
DOI: 10.3389/fbioe.2022.862395
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the 3D-Microstructure Between Alveolar and Iliac Bone for Enhanced Bioinspired Bone Graft Substitutes

Abstract: In oral- and maxillofacial bone augmentation surgery, non-vascularized grafts from the iliac crest demonstrate better clinical performance than alveolar bone grafts. The underlying mechanisms are not fully understood but are essential for the enhancement of bone regeneration scaffolds. Synchrotron Radiation µ-CT at a pixel size of 2.3 μm was used to characterize the gross morphology and the vascular and osteocyte lacuna porosity of patient-matched iliac crest/alveolar bone samples. The results suggest a differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 97 publications
1
11
0
Order By: Relevance
“…However, there are also studies showing the opposite: Rothweiler et al compared the three-dimensional microstructure of alveolar and iliac bone and found a greater distance from mineralized tissue to the closest pore-vessel boundary in alveolar bone, which was associated with a worse regenerative potential of the alveolar bone [ 29 ]. Also, the more rapid proliferation of orofacial human bone marrow stromal cells in vitro could not be proven in vivo, where iliac crest cells formed more compacted bone and were more responsive to osteogenic induction [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also studies showing the opposite: Rothweiler et al compared the three-dimensional microstructure of alveolar and iliac bone and found a greater distance from mineralized tissue to the closest pore-vessel boundary in alveolar bone, which was associated with a worse regenerative potential of the alveolar bone [ 29 ]. Also, the more rapid proliferation of orofacial human bone marrow stromal cells in vitro could not be proven in vivo, where iliac crest cells formed more compacted bone and were more responsive to osteogenic induction [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Small osseous defects are frequently augmented with xenogenic, allogenic or synthetic materials, yet autologous bone grafts remain mandatory for the reconstruction of large defects (>5 mm) [29,30]. These autologous bone grafts can be harvested from different anatomical sites, for example, mandibula, iliac crest or fibula, underlying biological differences have been discussed on the macro-and microstructural level [31][32][33]. Research on the molecular characteristics of alveolar bone is still in its infancy.…”
Section: Proteomic Assessment Of Peri-implant Hard Tissue (Bone Graft...mentioning
confidence: 99%
“…The microstructure of the mandible also differs from that of other bones. Compared with the iliac, the cortical bone of the mandible has a smaller vessel surface to bone volume ratio, and therefore a lower vessel porosity (Rothweiler et al, 2022) Frontiers in Physiology frontiersin.org and lacuna distribution have a more heterogeneous spatial distribution in the mandible than in the tibia or femur (Hesse et al, 2014). There is a higher bone density surrounding the mandibular LCN (Hesse et al, 2015).…”
Section: Morphophysiology and Biomechanicsmentioning
confidence: 99%
“…When mandibular grafts are used, there is a slower vertical loss of the graft; furthermore, they have a lower incidence of peri-implantitis (Kang et al, 2015) and a higher implant survival rate (Sbordone et al, 2009). However, when grafts larger than 5 mm are needed, iliac bone grafts can lead to better results, as they have a structure that allows greater blood perfusion, a necessary trait for larger grafts (Troeltzsch et al, 2016;Rothweiler et al, 2022).…”
Section: Clinical Aspectsmentioning
confidence: 99%